Acute and post-acute COVID-19 presentations in athletes: a systematic review and meta-analysis - Lemes, I. R.; Smaira, F. I.; Ribeiro, W. J. D.; Koenig Favero, N.; Nagem Janot Matos, L. D.; Lúcia de Sá Pinto, A.; Dolan, E.; Gualano, B. (British Journal of Sports Medicine, 2022)
Objective To describe acute/postacute COVID-19 presentations in athletes.